2012
DOI: 10.1177/205157071202700303
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding and Measurement of Consumer Hoarding

Abstract: Consumers are often faced with the question of what to do with objects that are still usable but not worth selling and for which they no longer have a use. Our paper shows that some consumers have a tendency to keep them rather than dispose of them. Two qualitative studies and nine quantitative studies were conducted to analyze this recurring behavior and to propose a consumer hoarding scale composed of four dimensions (instrumental, social, economic and sentimental). We show that this hoarding tendency may hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 93 publications
0
23
0
1
Order By: Relevance
“…They have shown that when personal control is threatened, individuals who need to control their environment set up boundaries in their environment to regain control (Cutright 2012;Strube and Werner 1984). Theses studies provide insight into understanding disposition and hoarding behavior (Guillard and Pinson 2012;Maycroft 2009).…”
Section: Untidinessmentioning
confidence: 96%
“…They have shown that when personal control is threatened, individuals who need to control their environment set up boundaries in their environment to regain control (Cutright 2012;Strube and Werner 1984). Theses studies provide insight into understanding disposition and hoarding behavior (Guillard and Pinson 2012;Maycroft 2009).…”
Section: Untidinessmentioning
confidence: 96%
“…Several studies have confirmed the reliability and validity of the HRS and it has been shown to be strongly correlated with related measures (Tolin et al, 2010;Tolin et al, 2018). Guillard and Pinson (2012) measured consumers' hoarding tendency using the following items: 'I usually tend to keep assets', 'I'm someone who likes to keep products rather than dispose of them' and 'I would like to keep everything if I could'. They distinguish between instrumental motives for hoarding (thoughts such as 'I might need it one day'), emotional motives ('it reminds me of things I did'), social motives ('it might be useful to someone') and economic motives (throwing things away feels like a waste of money) (Guillard & Pinson, 2012).…”
Section: Measurement Of Hoardingmentioning
confidence: 99%
“…Guillard and Pinson (2012) measured consumers' hoarding tendency using the following items: 'I usually tend to keep assets', 'I'm someone who likes to keep products rather than dispose of them' and 'I would like to keep everything if I could'. They distinguish between instrumental motives for hoarding (thoughts such as 'I might need it one day'), emotional motives ('it reminds me of things I did'), social motives ('it might be useful to someone') and economic motives (throwing things away feels like a waste of money) (Guillard & Pinson, 2012). Guillard and Pinson (2012) focused on what people think and feel about the disposal of assets; their measure does not cover other dimensions of hoarding and focuses on the motives leading to hoarding.…”
Section: Measurement Of Hoardingmentioning
confidence: 99%
“…Since motivations are positive antecedents, we expect them to be negatively correlated with impediments which are negative antecedents. We therefore correlated the ORM dimensions to 'product attachment' which we measured by adapting Guillard and Pinson's (2012) Tendency to Keep Everything measurement scale; as well as 'perceived risk associated with online resale website' and 'financial risk', by developing items based on Manchanda and Chu's (2013) and Xinyan and Xingjing's (2010) studies on online resale impediments. These items were measured on 10point Likert scales.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Secondly, Chu and Liao (2007) identified "resale after temporary ownership" as a specific type of planned resale. It might be interesting to use ORM in conjunction with other relevant constructs such as consumer hoarding (Guillard and Pinson, 2012) or materialism (Belk, 1985), in order to identify the tipping point or the critical point at which consumers start to consider reselling the product. Since our study established a link between ORM and online frequency it may be theorized that the period of usage of the product is inversely proportional to the online resale motivational level, but positively proportional to hoarding or materialism scores.…”
Section: Limitations and Future Research Avenuesmentioning
confidence: 99%